A tale of three houses - Saini, Yvonne (SAGE Knowledge. Cases., 2016)
The first thing Thandie Dhlomo, sales partner at the Rawson Property Group, did when she arrived home on a chilly Friday evening in July 2016 was pour herself a glass of red wine, kick off her shoes and curl up on her couch. She felt exhausted. Her last clients for the day had been Lunga Dlamini and his wife, Sonia. They were looking to move out of their rented house in Soweto and purchase their first home in one of the suburbs of Johannesburg. Dhlomo had helped them to narrow it down to three properties in three different suburbs: Linden, Parkhurst and Fourways. Dhlomo had just shown the couple the Linden property for the second time. Personally, she favoured the Parkhurst property as she felt that it was perfect for the family, but it was also the most expensive property of the three and she suspected that the Dlaminis had not been convinced. Dhlomo wondered what strategy she could use to persuade the Dlaminis that the Parkhurst property was the right fit for them.